1997
DOI: 10.1073/pnas.94.11.5804
|View full text |Cite
|
Sign up to set email alerts
|

Stable gene transfer and expression of human blood coagulation factor IX after intramuscular injection of recombinant adeno-associated virus

Abstract: We sought to determine whether intramuscular injection of a recombinant adeno-associated virus (rAAV) vector expressing human factor IX (hF.IX) could direct expression of therapeutic levels of the transgene in experimental animals. High titer (10 12 -10 13 vector genomes͞ ml) rAAV expressing hF.IX was prepared, purified, and injected into hindlimb muscles of C57BL͞6 mice and Rag 1 mice. In the immunocompetent C57BL͞6 mice, immunof luorescence staining of muscle harvested 3 months after injection demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
339
2
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(368 citation statements)
references
References 25 publications
23
339
2
2
Order By: Relevance
“…18,41 Skeletal muscle in particular has been used successfully for long -term expression of transgenes by rAAV. 21,30,42,43 When this approach was taken in the present investigation, it was observed that a single intramuscular injection of the rAAVHuEndo vector could lead to elevated serum endostatin levels by 4 weeks after injection (Fig 7 ). The endostatin levels reached a plateau value by 6 to 8 weeks (Fig 7) and were maintained as long as 4 months after injection.…”
Section: Discussionmentioning
confidence: 78%
“…18,41 Skeletal muscle in particular has been used successfully for long -term expression of transgenes by rAAV. 21,30,42,43 When this approach was taken in the present investigation, it was observed that a single intramuscular injection of the rAAVHuEndo vector could lead to elevated serum endostatin levels by 4 weeks after injection (Fig 7 ). The endostatin levels reached a plateau value by 6 to 8 weeks (Fig 7) and were maintained as long as 4 months after injection.…”
Section: Discussionmentioning
confidence: 78%
“…It should be noted that this decline in expression in baboons has not been seen in rodent models following intramuscular injection. 10,[12][13][14][15][16] We did not see a decline in hematocrit which corresponded to the decline in serum Epo levels. Since it has been 16 weeks (112 days) from the initial decline in Epo levels, it is unlikely that this continued elevation of hematocrit is due to the slow turnover (life span of approximately 120 days) of red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 There are five recent reports demonstrating the potential of sustained gene delivery following administration of rAAV vectors in mouse muscle. 10,[12][13][14][15] We have recently demonstrated the complete correction of a metabolic disease in a mouse model by a single intramuscular injection of rAAV expressing leptin. 16 In most of these reports there is evidence of long-term expression of the transgene following a single dose administration into mouse skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] In treated muscle of immunocompetent mice, this expression was shown to persist for 1.5 years. 19 Potentially therapeutic proteins that have been shown to be delivered and expressed by AAV vectors include erythropoietin, 20 cystic fibrosis transmembrane conductance regulator, 22 blood coagulation factor IX, 23,24 and GUS. 21 In none of these cases, however, were experiments designed to show that the AAV-mediated gene therapy actually affected the long-term course of a disease.…”
Section: Introductionmentioning
confidence: 99%